Next the Sea: Eccles and the Anthroposcenic. (October 2018) - Matless, David
Abstract: This paper considers the Anthroposcenic, whereby landscape becomes emblematic of processes marking the Anthropocene, through a specific site, Eccles on the northeast coast of Norfolk, England. The coast has become a key landscape for reflections on the Anthropocene, not least through processes of erosion and sea level change; the title phrase 'next the sea' here carries both spatial and temporal meaning. Through Eccles the paper investigates cultural-historical Anthropocene signatures over the past two centuries. Between 1862 and 1895 a church tower stood on Eccles beach; in preceding decades the tower was half-buried in sand dunes, but emerged after these were eroded by the sea. In 1895 the tower fell in a storm, although fragments remained intermittently visible over the following century, depending on the state of the beach. The paper takes Eccles tower as a focus for the exploration of themes indicative and/or anticipatory of the Anthropocene, including sea defence and geological speculation on land and sea levels, Eccles featuring in Charles Lyell's Principles of Geology . The tower became a visitor attraction, and discussions around the 1895 fall are examined, in relation to the spectacle of ruin, claims over the site and anxieties over defence. The periodic beach exposure of bones from the former churchyard prompted reflections on mortality, also present in literary engagements with Eccles by figures such as Henry Rider Haggard. The paper traces the persistence of fragmentary ruin memory through twentieth-century sea defence initiatives, and the ways in which late twentieth-century concerns for climate change and sea level rise generated a rediscovery of the site, yet also led to its effective disappearance as the beach built up following new sea defence construction. Eccles beach speaks to twenty-first-century preoccupations, aspects of its history over two hundred years making it emblematically Anthroposcenic. Highlights: Demonstrates the idea of the Anthroposcenic through the study of a specific site. Examines the cultural-historical signatures of the Anthropocene. Provides a detailed cultural-historical geography of an iconic coastal landscape. Combines analysis of scientific, literary, journalistic and visual source material.